2023
DOI: 10.3390/su15032399
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Tourists’ Intentions to Revisit Medical Destinations in the Post-COVID-19 Era through the Promotion of Their Clinical Trust and Well-Being

Abstract: The cross-border medical-care industry has recently grown exponentially, and medical-tourism development has been an integral part of the marketing strategies of medical institutions. However, having a successful medical-tourism destination that best attracts customers might be difficult to attain, particularly in the context of scarce relevant literature. Participants’ intentions to revisit a medical-tourism destination is better guided by the interplay of several factors, particularly clinical trust and well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The results of this study are in contrast to research conducted by (Guha et al, 2021) and (Moslehpour et al, 2021), which shows that brand image can influence purchase intention, which in this study is visit intention. The absence of influence of brand image on visit intention is supported by research from (Abdul-Rahman et al, 2023), which found that the brand image of the community health center did not influence the patient's revisit intention because many patients were hesitant to visit health services since the Covid-19 pandemic. 19 to prevent transmission.…”
Section: H8: Brand Image Has a Positive Effect On Visit Intentionmentioning
confidence: 96%
“…The results of this study are in contrast to research conducted by (Guha et al, 2021) and (Moslehpour et al, 2021), which shows that brand image can influence purchase intention, which in this study is visit intention. The absence of influence of brand image on visit intention is supported by research from (Abdul-Rahman et al, 2023), which found that the brand image of the community health center did not influence the patient's revisit intention because many patients were hesitant to visit health services since the Covid-19 pandemic. 19 to prevent transmission.…”
Section: H8: Brand Image Has a Positive Effect On Visit Intentionmentioning
confidence: 96%
“…In addition, research on tourism infrastructure and its effect on revisit intention, including studies of infrastructure in a wine destination (Bonn et al, 2016), medical destination (Abdul- Rahman et al, 2023), airport infrastructure (Seetanah et al, 2020), and travel infrastructure (Acharya et al, 2023) have revealed that high-quality infrastructure can influence tourist intentions to revisit a destination. The overall quality of infrastructure can be categorized as a predictor of tourist loyalty.…”
Section: Infrastructure On Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…Social media might also have a role in influencing tourists' trust (Javed et al 2020). Ideally, tourists can interact with destination stakeholders, such as tourism boards, travel agencies, and local businesses, which can further influence their trust in the destination, and this might be affected by service quality parameters (Abdul-Rahman et al 2023). Evidence has shown that trust in tourism destinations (as developed by social media influencers) has a positive impact on every stage of travel decision-making (Pop et al 2022).…”
Section: The Effect Of Social Media On Tourists' Intentions Value And...mentioning
confidence: 99%